The Influence of Silica Dioxide and Aluminum Oxide Nano Fillers Reinforced Heat Cured Acrylic Denture Base Material and Thermocycling on Tensile and Shear Bond to Denture Soft Lining Material (Mustansiria Dental Journal, 2019)
Background: Soft lining materials play an important role in modern prosthodonticstreatment because of their capability to restore the inflamed and distorted mucosa.The purpose of the research was to estimate the influence of acrylic denture basereinforcement with silanted nano fillers (Al2O3 and Sio2) separately on tensile andshear bond strength of soft lining material and studying effect of thermo cyclingon bonding strength.Materials and methods: Total 120 specimens were prepared; it divided into 60Specimens for shear bond strength test and 6o specimens for tensile bond strengthtest. Specimens were sub grouped into 30 Specimens without thermo cycling and30 specimens with thermo cycling. Each sub group is consisted from: 10Specimens control, 10 specimens were reinforced with 2 wt% of Al2O3 nano fillersand 10 specimens were reinforced with 5 wt% of SiO2 nano fillers. Samples wereprocessed depending on test applied. Soft lining material was applied for eachtesting group. Samples were immersed in distal water for 24 hours at 37°C beforetesting. For thermo cycling test, specimen were thermo cycled in thermo cyclingdevice. Bonding strength test was done using INSTRON universal testingmachine.Results: reinforcement of acrylic denture base with nano-fillers was significantlyincrease both tensile and shear bonding of lining material and thermo cyclingdecreases both bonding strength.Conclusion: reinforcement of acrylic denture base with nano fillers could improvebonding strength of lining material, while thermo cycling had a deleterious effecton bonding strength.